On the reaction of diphenylketene with isocyanides. - Robertson, J; Bell, S; Krivokapic, A (2005)
The products obtained from the reaction of diphenylketene with a variety of isocyanides are shown to depend heavily on the concentration of diphenylketene; a high concentration results in the precedented dioxolane derivatives, at much lower concentrations the reactions follow an alternative course and polycyclic beta-lactams are generated by a cascade of formal pericyclic reactions.